2006
DOI: 10.3844/ajbbsp.2006.186.194
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Conditions for Measuring Dehydrogenase Activity of Aspergillus niger using TTC

Abstract: ABSTRACT:The suitability of the triphenyl tetrazolium chloride (TTC) for dehydrogenase activity measurement of the vegetative cells of the fungal species Aspergillus niger was investigated. The triphenyl formazan (TF) yield increased with the increases in TTC concentration, pH, temperature and incubation time within the studied ranges. The effects of individual parameters, as well as the combined effects, on the TF yield were found to follow exponential expressions. The sensitivity analysis showed that the TF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Similar results were reported by Rao et al (1995). Ghaly and Mahmoud (2006) reported a TKN reduction of 55.6% after 60 days during in-vessel bioremediation process of hydrocarbons contaminated soil. Spinelli et al (2005) reported a slower reduction of 25% in TKN (from 10 mg kg −1 −o 7.5 mg kg −1 ) during in-vessel bioremediation of diesel contaminated soil mixed with food industry sludge after 170 days of bioremediation.…”
Section: Tknsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar results were reported by Rao et al (1995). Ghaly and Mahmoud (2006) reported a TKN reduction of 55.6% after 60 days during in-vessel bioremediation process of hydrocarbons contaminated soil. Spinelli et al (2005) reported a slower reduction of 25% in TKN (from 10 mg kg −1 −o 7.5 mg kg −1 ) during in-vessel bioremediation of diesel contaminated soil mixed with food industry sludge after 170 days of bioremediation.…”
Section: Tknsupporting
confidence: 80%
“…Spinelli et al (2005) reported a slower reduction of 25% in TKN (from 10 mg kg −1 −o 7.5 mg kg −1 ) during in-vessel bioremediation of diesel contaminated soil mixed with food industry sludge after 170 days of bioremediation. Ghaly and Mahmoud (2006) reported 61% reduction in TKN while composting greenhouse tomato plant residues with dairy manure.…”
Section: Tknmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the fact that the global microbiologic activity of the soil, and implicitly the DH activity -as biomarker of the degradation and reparation processes, are strongly influenced by a series of biotic and abiotic factors as the mining, the time and the temperature of incubation, the type of soil, the season, the loosening/aeration degree of the soil, its pH, the humidity, the management and maintenance practices [73][74][75][76][77] , the soil's fertilization, the deepness profile of the soil, the presence of different heavy metals etc. [78][79][80][81][82] , we resorted at the actual (Dha) and potential (Dha) dehydrogenase activity determination in soil samples taken from two different deepness profiles.…”
Section: Resultsmentioning
confidence: 99%
“…They transfer hydrogen and electrons through a chain of intermediate electron carriers to oxygen as a final electron acceptor, which subsequently combine with them to form water [30]. Dehydrogenase activity is largely measured using the triphenyl tetrazolium chloride (TTC) salt as a hydrogen acceptor.…”
Section: Discussionmentioning
confidence: 99%